A case study of Lebanese mathematics teachers' beliefs about curriculum integration and the sources of their beliefs - Khoury, Hala Ibrahim (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2007)
Teachers' beliefs about mathematics play a significant role in shaping their beh avior, teaching practices and student's learning. Recent reform efforts have adv ocated a new vision of mathematics, teaching mathematics through an integrated a pproach; it is unclear how teachers actually conceptualize what is meant by curr iculum integration and the sources of their beliefs. The purpose of this study i s to investigate the beliefs of elementary mathematics Lebanese teachers about c urriculum integration and the sources of their beliefs. This study was guided by the following questions: What are the beliefs of Lebanese elementary mathematic s teachers about the meaning of curriculum integration and how it could best be done at the elementary level? To what extent is what is good in the literature r eflected in the teachers' definitions of curriculum integration and task selecti on? What are the possible sources of Lebanese mathematics teachers' beliefs abou t integration? The research questions were investigated using a belief questionnaire, a task s orting activity and an interview administered to 6 Lebanese Elementary Mathemati cs teachers from two schools, one following an International curriculum and the other following the Lebanese curriculum. Findings suggest that those Lebanese te achers hold different views about integration, similar to those in the literatur e. It was also found that there is somehow a discrepancy between teachers? belie fs and their definitions about integration. The most influential sources of tho se teachers? beliefs are positive interaction with colleagues and the research d one by the teacher. A pattern was found between teachers? beliefs, definition ab out integration and the sources of their beliefs. The results of this study will be of interest for teachers, school administrato rs and curriculum writers. Findings from the present study would help researcher s to develop tools that help teachers reflect on their own beliefs, as well as d evelop instruments that can be used to survey teachers' beliefs about a specific issue, integration this case. Moreover, results from this study will contribute to the existing literature base on the relationship between beliefs about innov ations in education and practice. Some issues still need more investigation such as the sources of teachers' beliefs ...
: Mémoire
Keywords: Curriculum; L enseignement du Maths; Les Attitudes et conceptions des enseignants; Math education Curricula; Teachers attitudes and conceptions